2008
DOI: 10.1038/ng.129
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase is a susceptibility factor for heart failure in a rat model of human disease

Abstract: We aimed to identify genetic variants associated with heart failure by using a rat model of the human disease. We performed invasive cardiac hemodynamic measurements in F2 crosses between spontaneously hypertensive heart failure (SHHF) rats and reference strains. We combined linkage analyses with genome-wide expression profiling and identified Ephx2 as a heart failure susceptibility gene in SHHF rats. Specifically, we found that cis variation at Ephx2 segregated with heart failure and with increased transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 49 publications
8
119
0
Order By: Relevance
“…Furthermore, as NO 2 -OA did not elevate EETs or lower BP in KI mice, it was ineffective in preventing cardiac hypertrophy. These observations are consistent with several studies that show pharmacological inhibition of sEH can limit cardiac hypertrophy secondary to hypertension (6,14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, as NO 2 -OA did not elevate EETs or lower BP in KI mice, it was ineffective in preventing cardiac hypertrophy. These observations are consistent with several studies that show pharmacological inhibition of sEH can limit cardiac hypertrophy secondary to hypertension (6,14).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the therapeutic potential of hydrolase inhibitors, sEH null mice are protected from pathological interventions (13). Conversely, genetic alterations that promote enhanced hydrolase activity are a risk factor for human heart failure (14).…”
mentioning
confidence: 81%
“…Ephx2 is a susceptibility gene for hypertension-associated heart failure in rodents (39), and likewise, an association between single-nucleotide polymorphisms (SNPs) in Ephx2 gene and cardiovascular diseases (56). For instance, the K55R allele is associated with a higher risk of hypertension and ischemic stroke, as well as coronary heart disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…(1) The Ephx2 haplotype and expression pattern in WKY/Bbb appeared discrepant between Corenblum et al 15 and Monti et al 16 (2) Although the expression was low, it was still significantly greater than that of the SHRSP/Bbb. 16 u, unpublished observation by Nabika et al…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 95%
“…15 An independent study by Monti et al 16 showed that a genetic variation in the Ephx2 promoter and the resulting change in sEH expression influenced the susceptibility to heart failure in SHHF, which is a model rat for heart failure derived from SHRSP.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 99%